Negative electrode material and battery
Patent Information
- Application Number
- CN202510571655.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0031]本申请提供的负极材料,包括硅基活性物质及其表面的碳材料,由于负极材料内掺入了金属元素T,导致硅晶格变形,特别是位于硅基活性物质表层区域的晶格发生畸变,碳材料与硅基活性物质的接触界面增大,硅基活性物质与碳材料的结合强度提升,能够承受硅基活性物质脱嵌锂产生的体积膨胀及缩小。此外,硅基活性物质的表层区域发生晶格畸变,在此区域沉积、生长的碳材料与常规的碳材料相比,能同时兼顾强度与韧性,这样的碳材料粘覆在硅基活性物质颗粒表面,能够更好地缓冲硅基活性物质颗粒的体积变化,保持硅基活性物质颗粒表面的完整性,进一步提升负极材料的存储稳定性能。拉曼测试测得的A值可以用于表征负极材料表面的韧性,测得的Fa值可以用于表征负极材料的强度。为了更好的缓解、改善硅基材料的较大体积变化和膨胀应力,需要附着在其表面的物质同时具有柔性和强度。韧性能承受其体积变化,强度可以缓冲应力,但二者需要达成平衡,才能实现负极材料性能的更好发挥。本申请通过定义负极材料的表面柔韧度R值并限定其取值范围,来表征负极材料表面的碳材料质量。在金属元素T掺杂提高碳材料和硅基活性物质的结合强度的同时,本申请控制负极材料的表面柔韧度R值在0.08~0.5范围内,可以保障硅基活性物质充分嵌锂,碳材料还可以能够承受硅基活性物质的体积膨胀及收缩,硅基活性物质表面的碳材料能够兼具优异的韧性和强度,减少负极材料表面裂纹的产生。负极材料在具备优异的首次库伦效率及比容量的同时,还能够改善存储容量保持率及循环容量保持率。
Smart Images

Figure CN123017904A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of negative electrode material technology, specifically to negative electrode materials and batteries. Background Technology
[0002] Electrified new energy vehicles represent the future direction of the automotive market, and their core component is the lithium-ion battery. As the market develops, the demand for high-capacity batteries is increasing, and adopting novel high-specific-capacity positive and negative electrode materials is one of the important methods to improve battery energy density.
[0003] Silicon-based anode materials are a class of materials with silicon as the main active component. They are considered the next generation of anode materials due to their ultra-high theoretical specific capacity (4200 mAh / g), low lithium depletion potential (<0.5V), and slightly higher voltage plateau than graphite. Silicon is also less prone to surface lithium plating during charging, resulting in better safety performance and making them highly regarded. However, silicon anodes experience severe volume expansion during cycling, leading to material pulverization and breakage, and rapid battery degradation. The lower storage stability of silicon anodes compared to graphite anodes is also a significant factor limiting their commercialization.
[0004] As the silicon content in the negative electrode material gradually increases, the rapid capacity decay during storage becomes an insurmountable obstacle, and the battery's capacity rapidly decreases after being left for a long time after being fully charged.
[0005] Improving the storage capacity retention and cycle capacity retention of silicon anode materials, and mitigating battery capacity decay are urgent problems that need to be solved. Summary of the Invention
[0006] This application proposes an anode material and a battery. The anode material has suitable surface flexibility, and the carbon material on the surface of the anode material can better adapt to the volume expansion stress of the silicon-based active material. While possessing excellent first coulombic efficiency and specific capacity, the anode material can also improve storage capacity retention and cycle capacity retention.
[0007] In a first aspect, this application provides a negative electrode material, the negative electrode material comprising a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, the silicon-based active material comprising silicon and oxygen elements; the negative electrode material further contains a metal element T, T being selected from at least one of Zn, Ga, As, Sb, Sn, and Ag;
[0008] The mechanical strength of the negative electrode material was tested using atomic force microscopy, and the average mechanical strength of the negative electrode material was Fa GPa.
[0009] The negative electrode material was tested using Raman spectroscopy, and the negative electrode material was measured at 1345 cm⁻¹. -1 ~1365cm-1 The first characteristic peak exists within the wavelength range, at 1570 cm⁻¹. -1 ~1610cm -1 A second characteristic peak exists within the wavelength range, and the average value of the peak area ratio between the first characteristic peak and the second characteristic peak is A;
[0010] The surface flexibility of the negative electrode material is R = A / Fa, where 0.08 ≤ R ≤ 0.5.
[0011] In some implementations, 3 ≤ Fa ≤ 15; and / or, 1.2 ≤ A ≤ 2.5.
[0012] In some embodiments, the thermal conductivity of the negative electrode material is g1 W / (m·K) at 100°C and g2 W / (m·K) at 600°C. The coefficient of change of thermal conductivity of the negative electrode material is σ = (g2-g1) / 500, and 0.03% < σ < 0.5%.
[0013] In some implementations, 0.18 ≤ g1 ≤ 0.34.
[0014] In some implementations, 0.5 ≤ g2 ≤ 2.5.
[0015] In some embodiments, the hybridization degree ε of the negative electrode material is ε = K2 / K1, where K2 is the position of the highest peak intensity of the silicon characteristic peak measured by Raman spectroscopy, and K1 is the crystal orientation. <111> The position of the highest peak intensity of silicon characteristic peaks measured by Raman spectroscopy on a single-crystal silicon wafer, 0.8≤ε<1.
[0016] In some embodiments, the mass content of the metal element in the negative electrode material is ≤300ppm.
[0017] In some embodiments, the negative electrode material also includes other non-metallic elements.
[0018] In some embodiments, the other non-metallic elements include at least one of hydrogen and nitrogen, and the ratio of the number of carbon atoms to the total number of hydrogen and nitrogen atoms in the negative electrode material is (3-10):1.
[0019] In some embodiments, the other non-metallic elements include sulfur, and the ratio of the number of carbon atoms to the number of sulfur atoms in the negative electrode material is (2500-6500):1.
[0020] In some embodiments, the carbon material includes at least one of amorphous carbon and graphitized carbon.
[0021] In some embodiments, the carbon material forms a carbon layer on at least a portion of the surface of the silicon-based active material, the thickness of the carbon layer being <500 nm.
[0022] In some embodiments, the silicon-based active material includes at least one of elemental silicon, silicon oxide, and silicate.
[0023] In some embodiments, the silicon-based active material comprises silicon oxide, the general chemical formula of which is SiO. x , 0 < x ≤ 2.
[0024] In some embodiments, the silicon-based active material further includes at least one of silicates of element M and oxides of element M, wherein element M is selected from at least one of Mg, Al, and Li.
[0025] In some embodiments, the average grain size of the silicon grains in the negative electrode material is <20 nm.
[0026] In some embodiments, the water content in the negative electrode material is <0.5% by mass.
[0027] In some embodiments, the tap density of the negative electrode material is >0.5 g / cm³. 3 .
[0028] In some embodiments, the negative electrode material has a powder conductivity > 0.5 S / cm under a pressure of 20 kN.
[0029] Secondly, this application provides a battery comprising the negative electrode material described in the first aspect.
[0030] The technical solution of this application has at least the following beneficial effects:
[0031] The negative electrode material provided in this application includes a silicon-based active material and a carbon material on its surface. Due to the doping of the metal element T into the negative electrode material, the silicon lattice is deformed, particularly in the surface region of the silicon-based active material. This distortion increases the interface between the carbon material and the silicon-based active material, enhancing the bonding strength and enabling it to withstand the volume expansion and contraction caused by lithium insertion / extraction in the silicon-based active material. Furthermore, the lattice distortion in the surface region of the silicon-based active material allows for the deposition and growth of carbon material in this region, which, compared to conventional carbon materials, simultaneously maintains both strength and toughness. This carbon material, adhered to the surface of the silicon-based active material particles, better buffers the volume changes of the particles, maintains the integrity of the particle surface, and further improves the storage stability of the negative electrode material. The A value measured by Raman spectroscopy can be used to characterize the toughness of the negative electrode material surface, and the Fa value can be used to characterize its strength. To better alleviate and improve the large volume changes and expansion stress of the silicon-based material, the material attached to its surface needs to possess both flexibility and strength. Toughness can withstand volume changes, and strength can buffer stress, but a balance needs to be struck between the two to achieve better performance of the anode material. This application characterizes the quality of the carbon material on the surface of the anode material by defining the surface flexibility R value and limiting its range. While doping with metal element T improves the bonding strength between the carbon material and the silicon-based active material, this application controls the surface flexibility R value of the anode material within the range of 0.08 to 0.5. This ensures sufficient lithium intercalation into the silicon-based active material, and the carbon material can also withstand the volume expansion and contraction of the silicon-based active material. The carbon material on the surface of the silicon-based active material can possess both excellent toughness and strength, reducing the generation of surface cracks in the anode material. The anode material can not only have excellent initial coulombic efficiency and specific capacity, but also improve storage capacity retention and cycle capacity retention. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the discharge state of a battery provided in an embodiment of this application.
[0033] Figure 2 This is an atomic force microscope (AFM) image of the negative electrode material prepared in Example 1 of this application. Detailed Implementation
[0034] The following are preferred embodiments of the present invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the protection scope of the present invention.
[0035] In a first aspect, this application provides a negative electrode material, the negative electrode material comprising a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, the silicon-based active material comprising silicon and oxygen elements; the negative electrode material further contains a metal element T, T being selected from at least one of Zn, Ga, As, Sb, Sn, and Ag;
[0036] The mechanical strength of the negative electrode material was tested using atomic force microscopy, and the average mechanical strength of the negative electrode material was Fa GPa.
[0037] The negative electrode material was tested using Raman spectroscopy, and the negative electrode material was measured at 1345 cm⁻¹. -1 ~1365cm -1 The first characteristic peak exists within the wavelength range, at 1570 cm⁻¹. -1 ~1610cm -1 A second characteristic peak exists within the wavelength range, and the average value of the peak area ratio between the first characteristic peak and the second characteristic peak is A;
[0038] The surface flexibility of the negative electrode material is R = A / Fa, where 0.08 ≤ R ≤ 0.5.
[0039] The negative electrode material provided in this application includes a silicon-based active material and a carbon material on its surface. Due to the doping of the metal element T into the negative electrode material, the silicon lattice is deformed, particularly in the surface region of the silicon-based active material. This distortion increases the interface between the carbon material and the silicon-based active material, enhancing the bonding strength and enabling it to withstand the volume expansion and contraction caused by lithium insertion / extraction in the silicon-based active material. Furthermore, the lattice distortion in the surface region of the silicon-based active material allows for the deposition and growth of carbon material in this region, which, compared to conventional carbon materials, simultaneously maintains both strength and toughness. This carbon material, adhered to the surface of the silicon-based active material particles, better buffers the volume changes of the particles, maintains the integrity of the particle surface, and further improves the storage stability of the negative electrode material. The A value measured by Raman spectroscopy can be used to characterize the toughness of the negative electrode material surface, and the Fa value can be used to characterize its strength. To better alleviate and improve the large volume changes and expansion stress of the silicon-based material, the material attached to its surface needs to possess both flexibility and strength. Toughness can withstand volume changes, and strength can buffer stress, but a balance needs to be struck between the two to achieve better performance of the anode material. This application characterizes the quality of the carbon material on the surface of the anode material by defining the surface flexibility R value and limiting its range. While doping with metal element T improves the bonding strength between the carbon material and the silicon-based active material, this application controls the surface flexibility R value of the anode material within the range of 0.08 to 0.5. This ensures sufficient lithium intercalation into the silicon-based active material, and the carbon material can also withstand the volume expansion and contraction of the silicon-based active material. The carbon material on the surface of the silicon-based active material can possess both excellent toughness and strength, reducing the generation of surface cracks in the anode material. The anode material can not only have excellent initial coulombic efficiency and specific capacity, but also improve storage capacity retention and cycle capacity retention.
[0040] When the surface flexibility R of the negative electrode material is greater than 0.5, the carbon material on the surface of the negative electrode material is highly flexible, but its resistance to deformation decreases, making it difficult to withstand the stress impact brought by lithium intercalation into the silicon-based active material. After lithium intercalation, the carbon material on the surface of the negative electrode material particles fractures and microcracks appear, generating more new interfaces. This causes the SEI film to be repeatedly formed during the charging and discharging process of the manufactured battery, increasing the irreversible consumption of active lithium ions and accelerating capacity decay during storage. Furthermore, the fractured carbon material layer reduces the conductivity of the silicon-based active material surface, decreasing the ability of lithium ions to migrate into the silicon-based active material, thus reducing the capacity utilization of the negative electrode material. When the surface flexibility R of the negative electrode material is less than 0.08, the carbon material layer on the surface of the negative electrode material becomes more brittle, with weak stress buffering capacity. It is more prone to cracking and breakage when faced with large external forces. Similarly, this causes the SEI film to be repeatedly formed during the charging and discharging process of the manufactured battery, increasing the irreversible consumption of active lithium ions and accelerating capacity decay during storage.
[0041] In some embodiments, 3 ≤ Fa ≤ 15, and the average mechanical strength of the negative electrode material can specifically be 3 GPa, 4 GPa, 6 GPa, 8 GPa, 10 GPa, 12 GPa, 13 GPa, or 15 GPa, etc., and of course, other values within the above range are also possible, which are not limited here. The resistance of the negative electrode material to external stress is related to the mechanical strength of the carbon material on its surface. The larger the Fa value, the stronger the brittleness, and the easier it is to break under large external forces. Controlling the average mechanical strength of the negative electrode material within the above range can improve the structural stability of the negative electrode material, allowing it to withstand its own huge volume changes during charge-discharge cycles, reducing particle breakage, and improving the cycle capacity retention rate and storage capacity retention rate of the negative electrode material. When the average mechanical strength Fa of the negative electrode material is too large, the surface rigidity of the negative electrode material is too large, the silicon-based active material is too tightly bound by the carbon material, making it difficult to achieve lithium intercalation expansion, reducing the degree of lithium intercalation, and decreasing the capacity of the negative electrode material. When the average mechanical strength Fa of the anode material is too small, the carbon layer is unable to withstand the expansion stress of the silicon-based active material, which leads to the cracking of the carbon layer. As a result, the cycle capacity retention rate and storage capacity retention rate of the anode material will both decrease.
[0042] In some embodiments, the average value of the peak area ratio of the first characteristic peak to the second characteristic peak is A, where 1.2 ≤ A ≤ 2.5. The specific value of A can be 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 2.0, 2.2, 2.4, or 2.5, or other values within the above range, which are not limited here. When the peak area ratio A is too small, there are fewer defects on the surface of the negative electrode material, resulting in higher mechanical strength. While this is beneficial for lithium ion insertion / extraction, the increased surface rigidity of the negative electrode material makes the silicon-based active material too tightly bound by the carbon material, hindering lithium insertion expansion and reducing the degree of lithium insertion, thus decreasing the capacity of the negative electrode material. When the peak area ratio A is too large, the disorder of the carbon material decreases, and surface defects increase. During charging and discharging, under the volume expansion stress of the silicon-based active material, the carbon layer is prone to cracking and propagation from defects, leading to decreased mechanical strength and flexibility of the carbon layer. This exacerbates side reactions in the negative electrode material, resulting in accelerated capacity decay. This application controls the A value within the above range, which helps to ensure the specific capacity of the negative electrode material while improving the capacity retention rate of the negative electrode material.
[0043] When a battery containing a negative electrode material experiences thermal runaway, the ambient temperature of the negative electrode material can reach over 100°C. Therefore, this application tests the change in thermal conductivity of the negative electrode material at high temperatures of 100°C and extremely high temperatures of 600°C to verify the heat dissipation capability of the negative electrode material under high temperature conditions.
[0044] In some embodiments, the thermal conductivity of the negative electrode material at 100°C (i.e., 373.15K) is g1 W / (m·K), where 0.18 ≤ g1 ≤ 0.34. Specifically, the thermal conductivity of the negative electrode material at 100°C can be 0.18 W / (m·K), 0.2 W / (m·K), 0.25 W / (m·K), 0.28 W / (m·K), 0.3 W / (m·K), 0.32 W / (m·K), 0.34 W / (m·K), etc. Of course, it can also be other values within the above range, which are not limited here.
[0045] In some embodiments, the thermal conductivity of the negative electrode material at 600°C (i.e., 873.15K) is g2 W / (m·K), where 0.5 ≤ g2 ≤ 2.5. Specifically, the thermal conductivity of the negative electrode material at 600°C can be 0.5 W / (m·K), 0.8 W / (m·K), 1.0 W / (m·K), 1.2 W / (m·K), 1.5 W / (m·K), 1.8 W / (m·K), 2.0 W / (m·K), or 2.5 W / (m·K), etc. Of course, it can also be other values within the above range, which are not limited here.
[0046] In some embodiments, the thermal conductivity variation coefficient σ of the negative electrode material is σ = (g2-g1) / 500, where 0.03% < σ < 0.5%. Specifically, the thermal conductivity variation coefficient σ of the negative electrode material can be 0.031%, 0.04%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.35%, 0.4%, 0.45%, 0.48%, or 0.49%, etc., and can also be other values within the above range, without limitation. When σ ≤ 0.03%, the thermal conductivity of the negative electrode material is poor at different temperatures, making it difficult to quickly dissipate the heat generated during charging and discharging. The temperature difference hinders lithium-ion transport, exacerbating the capacity decay of the negative electrode material. When σ ≥ 0.5%, the thermal conductivity variation between different particles of the silicon-based active material becomes too large, making it difficult to maintain the good mechanical toughness of the anode material to resist volume changes during charging and discharging. This leads to particle breakage, structural collapse, accelerated loss of active lithium ions, capacity reduction, and rapid degradation of cycle performance. Doping the anode material with appropriate amounts of metal elements alters the crystal structure of silicon oxide to some extent, affecting the thermal vibration of the silicon oxide lattice and causing changes in the thermal conductivity of the anode material. When the thermal conductivity variation coefficient σ of the anode material is controlled within 0.03% < σ < 0.5%, the heat generated during charging and discharging can be conducted relatively quickly at different temperatures, reducing the uneven temperature difference within or between anode material particles. Furthermore, controlling the thermal conductivity variation coefficient within the above range ensures heat dissipation and conduction even in ultra-high temperature environments, improving the safety of batteries made from anode materials.
[0047] In some embodiments, the hybridization degree ε of the negative electrode material is ε = K2 / K1, where K2 is the position of the highest peak intensity of the silicon characteristic peak measured by Raman spectroscopy, and K1 is the crystal orientation. <111> The position of the highest peak intensity of silicon characteristic peaks measured by Raman spectroscopy on a single-crystal silicon wafer, 0.8 ≤ ε < 1. Specifically, K2 is located at 416 cm⁻¹ in the Raman spectrum. -1 ~519cm -1 At this point, K1 is located at 519.5 cm⁻¹ in the Raman spectrum. -1 ~520.5cm -1 Place.
[0048] Specifically, the hybridization degree ε of the anode material can be 0.8, 0.82, 0.85, 0.86, 0.88, 0.90, 0.92, 0.95, 0.94, 0.97, 0.99, or any value within a range thereof, and is not limited here. Understandably, since silicon-based active materials contain metal elements, compared to those with a crystal orientation of... <111> The standard position of the silicon characteristic peak of a single-crystal silicon wafer is determined by the fact that metal doping can cause the silicon characteristic peak to shift. This application controls the hybridization degree of the anode material within the aforementioned range, which is beneficial for controlling the metal element content in the anode material within a suitable range. This can improve the volume expansion of the anode material and enhance its specific capacity and first coulombic efficiency.
[0049] In some embodiments, the metal element T is selected from at least one of Zn, Ga, As, Sb, Sn, and Ag. For example, doping a silicon-based active material with Sb can improve its high-temperature stability, change its coefficient of thermal expansion, and reduce volume expansion.
[0050] In some embodiments, the mass content of the metal element T in the negative electrode material is ≤300ppm, specifically it can be 300ppm, 280ppm, 250ppm, 230ppm, 200ppm, 180ppm, 150ppm, 120ppm, 100ppm, 50ppm, 20ppm, etc., or any value within a range thereof, and is not limited herein. Excessive metal element content in the negative electrode material will lead to a decrease in the structural stability of the negative electrode material and will also increase the manufacturing cost.
[0051] In some embodiments, the silicon-based active material includes at least one of elemental silicon, silicon oxide, and silicates. Elemental silicon can be amorphous silicon and / or crystalline silicon, and silicates can be lithium silicates, magnesium silicates, aluminosilicates, etc.
[0052] In some embodiments, the silicon-based active material includes silicon oxide, which includes silicon and oxygen elements, with an atomic ratio of silicon to oxygen of 0 to 2, excluding 0.
[0053] In some embodiments, the silicon-based active material includes silicon oxide, the general chemical formula of which is SiO. x Where 0 < x ≤ 2. Specifically, SiO x Specifically, it could be SiO 0.5 SiO 0.7 SiO 0.9 SiO, SiO 1.2 SiO 1.5 SiO 1.8 SiO 1.9 etc., without limitation. Silicon oxide can be represented by the general formula SiO. x (0 < x ≤ 2). It can be a material formed by silicon dispersed in SiO2, or silicon particles dispersed in SiO, with the interface between the two being SiO2. x However, it is not limited to this.
[0054] In some embodiments, the average particle size of the silicon grains in the negative electrode material is <20nm, specifically it can be 19nm, 15nm, 12nm, 10nm, 9nm, 7nm, 6.0nm, 5.5nm, 5.0nm, 4.5nm, 4.0nm, 3nm, 2nm, 1nm, etc., and is not limited here. It is understood that an average particle size of ≤20nm for the silicon grains in the negative electrode material is beneficial for the dispersed distribution of silicon grains, effectively reducing silicon volume expansion and improving cycle performance.
[0055] In some embodiments, the silicon-based active material further includes a metal element M, wherein the element M is selected from at least one of Mg, Al, and Li.
[0056] In some embodiments, the metal element M exists in at least one of the silicates of M and oxides of M. Understandably, the silicates of M and oxides of M are distributed in the silicon-based active material, and doping with metal M can improve the ion-conducting ability of the negative electrode material and enhance its structural strength. Preferably, M is Mg and / or Li.
[0057] In some embodiments, carbon material exists on the surface of the silicon-based active material and / or is dispersed between the silicon-based active material particles in the negative electrode material. Specifically, the silicon-based active material particles can be embedded within the carbon material as a matrix; alternatively, primary silicon-based active material particles can be granulated and coated to form secondary particles, which is not limited here. The carbon material constructs a conductive network for the silicon-based active material, overcoming the poor conductivity of the silicon-based active material and improving its capacity utilization and cycle stability.
[0058] In some embodiments, the carbon material includes at least one of amorphous carbon and graphitized carbon, wherein the amorphous carbon may be soft carbon and / or hard carbon, and it is understood that the carbon material can improve the conductivity of silicon-based active materials.
[0059] In some embodiments, carbon material forms a carbon layer on at least a portion of the surface of the silicon-based active material.
[0060] In some embodiments, the thickness of the carbon layer is <500nm, specifically it can be 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 400nm, 480nm, etc., and of course, other values within the above range are also possible, without limitation. It is understood that by limiting the thickness of the carbon layer within the above range, the carbon layer can more completely coat the silicon-based active material, reducing direct contact between the silicon-based active material and the electrolyte, thereby reducing the formation of the SEI film. It can also increase the conductivity of the negative electrode material, alleviate the volume expansion of the silicon-based active material, and is beneficial to improving the specific capacity and cycle stability of the negative electrode material.
[0061] In some embodiments, the negative electrode material further includes other non-metallic elements. In this application, these other non-metallic elements are at least partially doped into the carbon material, which can improve the mechanical strength of the carbon layer, enabling the carbon layer to withstand the expansion stress of the silicon-based active material, adapt to the volume expansion and contraction of the silicon-based active material, reduce the generation of carbon layer cracks, and improve the capacity retention rate of the negative electrode material.
[0062] In some embodiments, the other non-metallic elements include at least one of hydrogen and nitrogen, and the ratio of the number of carbon atoms to the total number of hydrogen and nitrogen atoms in the negative electrode material is (3 to 10):1; specifically, it can be 3:1, 4:1, 5:1, 6:1, 8:1, 9:1, 10:1, etc., or other values within the above range.
[0063] In some embodiments, the other non-metallic elements include sulfur, and the ratio of carbon atoms to sulfur atoms in the negative electrode material is (2500-6500):1, specifically 2500:1, 2600:1, 2800:1, 3000:1, 3500:1, 4000:1, 4500:1, 5000:1, 5500:1, 6000:1, 6500:1, etc., or other values within the above range.
[0064] This application controls the content of non-metallic elements in the negative electrode material, which helps to improve the mechanical strength of the carbon material on the surface of the negative electrode material. It is also beneficial to synergistically control the surface flexibility R of the negative electrode material within a suitable range, so that the carbon material can have both excellent toughness and strength, reduce the generation of surface cracks in the negative electrode material, and improve the storage capacity retention rate and cycle stability of the negative electrode material.
[0065] In some embodiments, the silicon content in the anode material is 48% to 63% by mass, specifically 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 60%, 61%, or 63%, etc., and other values within the above range are also possible, without limitation. When the silicon content is too low, the specific capacity of the anode material is low, making it difficult to meet the requirements of high-energy-density lithium-ion batteries; when the silicon content is too high, the volume expansion of the anode material is too large, leading to severe degradation of the material's cycle performance.
[0066] In some implementations, the tap density of the negative electrode material is >0.5 g / cm³. 3 Specifically, it can be 0.55g / cm 3 0.6g / cm 3 0.8g / cm 3 0.9g / cm 3 1.0g / cm 3 1.2g / cm 3 1.3g / cm 3 1.5g / cm 3 Or 2.0g / cm 3 Of course, other values within the above range are also possible and are not limited here. Controlling the tap density of the anode material within the above range is beneficial to improving the energy density and rate performance of the anode material.
[0067] In some embodiments, the powder conductivity of the negative electrode material under a pressure of 20 kN is >0.5 S / cm, specifically it can be 0.55 S / cm, 1 S / cm, 2 S / cm, 5 S / cm, 6 S / cm, 10 S / cm, 15 S / cm, or 20 S / cm, etc., and is not limited here. Controlling the powder conductivity of the negative electrode material within the above range is beneficial to improving the conductivity of the negative electrode material and reducing the resistivity of the negative electrode sheet.
[0068] In some embodiments, the water content in the negative electrode material is <0.5% by mass. Specifically, the water content can be 0.49%, 0.4%, 0.3%, 0.2%, 0.1%, 0.05%, 0.01%, etc., or other values within the above range, which are not limited here. Preferably, the water content in the negative electrode material is <0.1% by mass.
[0069] Secondly, this application provides a method for preparing a negative electrode material, the method comprising the following steps:
[0070] Step S10: Under vacuum conditions, the silicon-oxygen raw material is heated and vaporized and kept at a constant temperature. Then, a mixed gas containing a doped metal T source is introduced to carry out the doping reaction. The cooling rate is controlled at 50-120℃ / min to cool the reaction product to room temperature, thereby obtaining a silicon-oxygen bulk material doped with T atoms. T is selected from at least one of Zn, Ga, As, Sb, Sn, and Ag.
[0071] Step S20: The bulk silicon-oxygen material doped with T atoms is crushed and pulverized to obtain granular silicon-oxygen material. A doping gas source containing at least one of magnesium, aluminum, and lithium elements is introduced to carry out a secondary doping reaction. The introduced gas is switched to a mixed gas of carbon source gas and nitrogen-containing gas to carry out carbon coating treatment. After cooling, a negative electrode material is obtained. The negative electrode material includes silicon-based active material and carbon material.
[0072] The method for preparing the anode material provided in this application first involves heating and gasifying a silicon-oxygen raw material to generate silicon oxide. Then, a mixed gas containing a doped metal T source is introduced, causing the doped metal T atoms to be incorporated into the silicon oxide lattice. By controlling the cooling rate, the metal T atoms are ensured to be uniformly distributed within the silicon oxide, preventing aggregation or clustering during cooling. The particles of the T-doped silicon-oxygen bulk material are then further doped with metal, and finally, carbon coating is applied. During carbon coating, appropriate amounts of nitrogen (N) and hydrogen (H) elements are introduced to alter the electronic structure and chemical properties of the deposited carbon material, thereby improving its flexibility. This application, through doping the silicon-based active material and modifying the carbon material, enables the carbon material on the surface of the silicon-based active material to possess suitable flexibility and mechanical strength. The carbon material ensures sufficient lithium intercalation into the silicon-based active material and can withstand the volume expansion and contraction of the silicon-based active material, reducing the formation of surface cracks in the anode material. The anode material exhibits excellent initial coulombic efficiency and specific capacity, while also improving storage capacity retention and cycle capacity retention.
[0073] The preparation method provided in this scheme is described in detail below:
[0074] Step S10: Under vacuum conditions, the silicon-oxygen raw material is heated and vaporized and kept at a constant temperature. Then, a mixed gas containing a doped metal T source is introduced to carry out the doping reaction. The cooling rate is controlled at 50-120℃ / min to cool the reaction product to room temperature, thereby obtaining a silicon-oxygen bulk material doped with T atoms.
[0075] In some implementations, the silicon-oxygen raw material includes a silicon source and an oxygen source.
[0076] In some embodiments, the silicon source includes at least one of metallic silicon powder, silicon ore, silicon dioxide, polycrystalline silicon, and silicon slag.
[0077] In some embodiments, the oxygen source includes at least one of oxygen, ozone, carbon monoxide, carbon dioxide, and silicon dioxide.
[0078] In some embodiments, the vacuum pressure during the heating and vaporization process is less than or equal to 50 Pa, specifically 0.1 Pa, 1 Pa, 10 Pa, 20 Pa, 30 Pa, 40 Pa, 50 Pa, etc., and of course, other values within the above range are also possible, which are not limited here.
[0079] In some embodiments, the heating and vaporization temperature is 1000℃~1300℃, specifically 1000℃, 1100℃, 1200℃ or 1300℃, etc., and of course, other values within the above range are also possible, which are not limited here.
[0080] In some implementations, the heat preservation time is 30 min to 100 min, specifically 30 min, 50 min, 60 min, 80 min or 100 min, etc., and of course other values within the above range are also possible, which are not limited here.
[0081] In some embodiments, the heating rate of the silicon-oxygen raw material is 3℃ / min to 10℃ / min, specifically 3℃ / min, 5℃ / min, 6℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, etc., and of course, other values within the above range are also possible, which are not limited here.
[0082] In this application, by controlling the heating and vaporization temperature, holding time and heating rate of the silicon-oxygen raw material, the various components in the silicon-oxygen material can be fully contacted and reacted to form a silicon-oxygen block material with uniformly distributed components.
[0083] In some implementations, the boiling point of the doped metal T source is <1500°C.
[0084] In some embodiments, the doped metal T includes at least one of Zn, Ga, As, Sb, Sn, and Ag.
[0085] In some embodiments, the mixed gas containing the doped metal T source includes a carrier gas and a T source gas, wherein the flow rate of the mixed gas is 0.5 L / min to 10 L / min, specifically 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 5 L / min, 7 L / min, 8 L / min or 10 L / min, etc., and of course, other values within the above range are also possible, which are not limited here.
[0086] In some embodiments, the flow rate of the carrier gas is 5 to 20 times that of the flow rate of the T source gas, specifically 5 times, 10 times, 15 times or 20 times, etc., and of course, other values within the above range are also possible, which are not limited here.
[0087] In some embodiments, the carrier gas includes at least one of helium, neon, argon, xenon, and krypton.
[0088] In some embodiments, the doping reaction time is 10 min to 80 min, specifically 10 min, 30 min, 50 min, 60 min or 80 min, etc., and of course other values within the above range are also possible, which are not limited here.
[0089] In this application, the T source gas is introduced by a carrier gas. The addition of the carrier gas can change the distribution of the doped metal T source between the silicon source and the oxygen source, so that the doped metal T can be distributed more evenly in the silicon source material, thereby adjusting the magnitude of the expansion and contraction tension of the silicon-oxygen material.
[0090] In some embodiments, the cooling rate is 50℃ / min to 120℃ / min, specifically 50℃ / min, 60℃ / min, 70℃ / min, 80℃ / min, 90℃ / min, 100℃ / min, 110℃ / min or 120℃ / min, etc. Of course, other values within the above range are also possible, and are not limited here.
[0091] In this application, controlling the cooling rate within the aforementioned range ensures that the doped T element is uniformly distributed in the silicon oxide without agglomeration or clustering during cooling. Even during subsequent reheating, the relative positions of the metal T atoms and the silicon oxide remain largely unchanged.
[0092] Step S20: The bulk silicon-oxygen material doped with T atoms is crushed and pulverized to obtain granular silicon-oxygen material. A doping gas source containing at least one of magnesium, aluminum, and lithium elements is introduced to carry out a secondary doping reaction. The introduced gas is switched to a mixed gas of carbon source gas and nitrogen-containing gas to carry out carbon coating treatment. After cooling, a negative electrode material is obtained. The negative electrode material includes silicon-based active material and carbon material.
[0093] In some embodiments, the temperature of the secondary doping reaction is 600℃ to 1000℃, specifically 600℃, 800℃, 900℃ or 1000℃, etc., and of course other values within the above range are also possible, which are not limited here.
[0094] In some implementations, the secondary doping reaction time is 2h to 8h, specifically 2h, 4h, 5h, 6h or 8h, etc., and of course other values within the above range are also possible, which are not limited here.
[0095] In some embodiments, the volume ratio of carbon source gas to nitrogen-containing gas is 0.1 to 3, specifically 0.1, 0.5, 0.8, 1, 1.5, 2, 2.5 or 3, etc. Of course, other values within the above range are also possible, and no limitation is made here.
[0096] In some embodiments, the carbon source gas includes at least one of methane, ethane, ethylene, acetylene, propyne, propylene, propane, toluene, benzene, and styrene.
[0097] In some embodiments, the nitrogen-containing gas includes at least one of ammonia, nitrogen oxides, and nitrogen trifluoride.
[0098] In some embodiments, the flow rate of the mixed gas of carbon source gas and nitrogen-containing gas is 1.0 L / min to 10 L / min, specifically 1.0 L / min, 1.5 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 8 L / min or 10 L / min, etc. Of course, other values within the above range are also possible, and no limitation is made here.
[0099] In some embodiments, the carbon coating treatment temperature is 600℃ to 1000℃, specifically 600℃, 700℃, 800℃, 900℃ or 1000℃, etc., and of course other values within the above range are also possible, which are not limited here.
[0100] In some embodiments, the carbon coating treatment takes place for 2 hours to 10 hours, specifically 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours, or other values within the above range, which are not limited here.
[0101] In this application, carbon coating is applied to the surface of a silicon-based active material via vapor deposition, and nitrogen is introduced. This alters the deposition method and quality of the carbon material, changes its electronic structure, and improves its flexibility. By doping the silicon-based active material and modifying the carbon material, this application achieves a suitable level of flexibility for the carbon material on the silicon-based active material surface. The carbon material ensures sufficient lithium intercalation into the silicon-based active material and can withstand the volume expansion and contraction of the silicon-based active material, reducing the formation of surface cracks in the anode material.
[0102] In some embodiments, the preparation method further includes shaping, demagnetizing, and sieving the carbon-coated product.
[0103] Thirdly, this application provides a battery comprising the negative electrode material described in the first aspect or the negative electrode material prepared by the method described in the second aspect.
[0104] The battery provided in this application can be a secondary battery (such as a lithium-ion battery, sodium-ion battery, etc.), including a casing, electrode assembly, and electrolyte. Both the electrode assembly and electrolyte are located inside the casing. The casing can be a packaging bag sealed with an encapsulating film (such as an aluminum-plastic film), for example, a pouch battery for the secondary battery. In other embodiments, the secondary battery can also be a steel-cased battery, an aluminum-cased battery, etc. Figure 1 This is a schematic diagram of the discharge state of the battery provided in the embodiments of this application, such as... Figure 1As shown, the battery includes a casing and an electrode assembly. The electrode assembly includes a positive electrode 1, a negative electrode 2, and a separator 3, with the separator 3 disposed between the positive electrode 1 and the negative electrode 2. The electrode assembly can be a stacked structure, formed by alternately stacking the positive electrode 1, the separator 3, and the negative electrode 2. In other embodiments, the electrode assembly can also be a wound structure, formed by sequentially stacking and winding the positive electrode, the separator, and the negative electrode.
[0105] In some embodiments, the positive electrode 1 includes a positive current collector 101 and a positive active layer 102 disposed on at least one surface of the positive current collector 101.
[0106] In some embodiments, the positive current collector 101 may be made of aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as, but not limited to, current collectors formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) with a polymer substrate. The positive active layer 102 comprises a positive active material, which includes compounds that reversibly insert and deintercalate metal ions.
[0107] In some embodiments, the positive electrode active material may include lithium transition metal composite oxides, sodium transition metal composite oxides, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.
[0108] In some embodiments, the positive electrode active material may include, but is not limited to, lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary materials (NCM), lithium manganese oxide (LiMn2O4), and lithium nickel manganese oxide (LiNi). 0.5 Mn 1.5 At least one of lithium iron phosphate (LiFePO4) or lithium iron phosphate (LiFePO4).
[0109] In some embodiments, the negative electrode 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.
[0110] In some embodiments, the negative electrode current collector 201 can be at least one of copper foil, nickel foil, stainless steel foil, titanium foil, or carbon-based current collector, or any composite current collector disclosed in the prior art, such as, but not limited to, current collectors formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material described in the first aspect or the negative electrode material prepared by the aforementioned preparation method. The battery provided in this application embodiment has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance, and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., and is not limited thereto.
[0111] The embodiments of the present invention will be further described below with reference to several examples. However, the embodiments of the present invention are not limited to the specific embodiments described below. Appropriate modifications can be made within the scope of unchanged main claims. Test method:
[0112] (1) Raman test
[0113] The Raman spectra of the powder were tested using a Renishaw In Via microconfocal Raman spectrometer (Japan). The test parameters were: laser wavelength 532 nm, test range 100 cm⁻¹. -1 Up to 3000cm -1 At least 15 points were randomly selected to obtain multiple Raman spectral curves. After removing outlier curves, the remaining curves were analyzed. First, the curves located at 1345 cm⁻¹ were calibrated. -1 ~1365cm -1 The first characteristic peak (i.e., the D peak) at 1570 cm⁻¹ and the peak at 1570 cm⁻¹ -1 ~1610cm -1 The second characteristic peak (i.e., G peak) is located at the point. Then, the area of D peak and G peak is calculated by fitting the data using the software provided with the device. The area ratio of D peak and G peak corresponding to each curve is calculated, and finally, the average value of the area ratio is taken as the A value of the sample.
[0114] The position of the highest peak intensity of silicon characteristic peaks measured by Raman spectroscopy for the anode material is K2, and the crystal orientation is... <111> The position of the highest peak intensity of silicon characteristic peaks measured by Raman spectroscopy for a single-crystal silicon wafer is K1, and the hybridization degree of the anode material is ε = K2 / K1.
[0115] (2) Average mechanical strength test
[0116] Testing was performed using a Bruker Dimension ICON AFM instrument. A suitable sample was dispersed in ethanol to form a suspension with a concentration of 0.1–1 mg / mL. 10–50 μL of this suspension was then dispersed onto a silicon wafer and dried. Testing was then performed on the AFM instrument. The center of particles with a diameter >3 μm was selected for surface scanning (2 μm x 2 μm). The average mechanical strength of each tested area was calculated using the instrument's built-in software. Ten areas were randomly tested for each sample, and the average mechanical strength of these ten areas was taken as the average mechanical strength of the sample.
[0117] (3) Thermal conductivity variation coefficient test
[0118] The thermal conductivity was measured using a Hot Disk TPS2500S instrument in a nitrogen atmosphere at 100℃ and 600℃. Before testing, a suitable amount of powder sample was poured into a 30mm infrared mold and pressed into two samples at 20MPa. A suitable probe was selected, and the sample and probe were sandwiched together, with the probe's coil directly below the pressure screw. The two samples were placed flat against the probe, ensuring minimal gaps. The test parameters, measurement time, and power were adjusted to achieve a stable thermal conductivity value. Using this method, the thermal conductivity at 100℃ was measured as g1, and at 600℃ as g2. The coefficient of thermal conductivity variation was calculated as (g2 - g1) / 500, in W / (m·K).
[0119] (4) Dopant element content test
[0120] Testing instrument: Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES), PerKinElmer, Model Optima 2100DV. Weigh 0.3–0.5 g of sample, add 6 mL of hydrochloric acid and 2 mL of nitric acid, and heat on a graphite digester for approximately 30 minutes to completely digest the trace elements in the sample. After filtration and volume adjustment, the content of the metallic element T is determined using ICP-OES.
[0121] (5) Nitrogen and hydrogen content test
[0122] The elemental analysis was performed using an ONH-2000 elemental analyzer from ERT (Germany). The sample and flux were added together to a graphite crucible and heated to a maximum temperature of 3000°C to melt. N₂ and H₂ were generated by high-temperature decomposition. The N₂ and H₂ were measured by a carrier gas fed into a thermal conductivity cell. Nitrogen content testing was performed according to GB / T 20124-2006, "Determination of Nitrogen Content in Iron and Steel - Inert Gas Melting Thermal Conductivity Method (Conventional Method)". Hydrogen content testing was performed according to GB / T 4702.17-2016, "Determination of Oxygen, Nitrogen, and Hydrogen Content in Metallic Chromium - Inert Gas Melting Infrared Absorption Method and Thermal Conductivity Method".
[0123] (6) Trace carbon content and sulfur testing
[0124] The carbon and sulfur content was measured using an infrared carbon-sulfur analyzer (CSi). A certain amount of sample was weighed and placed in a ceramic crucible, flux was added, and the mixture was placed in a high-frequency furnace where high-purity oxygen was introduced for combustion to produce carbon dioxide and sulfur dioxide, etc. The carbon and sulfur content in the gas was determined by an infrared detector. For specific details, please refer to GB / T 20123-2006 "Determination of Total Carbon and Sulfur Content in Iron and Steel - Infrared Absorption Method After Combustion in a High-Frequency Induction Furnace (Conventional Method)".
[0125] (7) Powder conductivity test of negative electrode material:
[0126] The testing equipment was from Mitsubishi Chemical, Japan, model MCP-PD51. Test parameters included: initial resistance selectable to the order of -3, voltage limit selectable to 10V, sample thickness of 3–5 mm under 20 kN pressure, and pressure settings of 4, 8, 12, 16, and 20 kN. The electrode radius was 0.7 mm, and the sample radius was 10 mm.
[0127] (8) Test method for tap density of negative electrode material:
[0128] Referring to GB / T 5162-2006 / ISO 3953:1993 "Determination of tap density of metal powders", the tap density was tested using a Canta DAT-4-220 tap density analyzer manufactured by Anton Paar (Shanghai) Trading Co., Ltd. The tap density T is the value after 1000 vibrations. The feed weight was 60g, and the unit is g / cm³. 3 .
[0129] (9) Test method for water content of negative electrode material: The water content is determined according to the Karl Fischer method. A Mettler-Toledo coulometric titration moisture analyzer is used for testing. ① Sample amount: 0.5g~1.0g. ② Sample preparation: Place a clean sample bottle on the analytical balance and zero it. Then add the sample to the sample bottle, record the sample weight, seal it with special aluminum foil, and cover it with a plastic cap. ③ Sample testing: Place the sealed sample bottle into the cassette furnace of the moisture analyzer and heat it at 200℃ to turn the water in the sample into water vapor, which is then carried into the analysis cell of the moisture analyzer by the drying carrier gas for testing. ④ Recording results: Read the data and record the test results. The test results are accurate to 0.001%.
[0130] (10) Test method for carbon layer thickness: The negative electrode material is cut by an ion mill and the carbon coating thickness on the material surface is measured in SEM.
[0131] (11) Methods for measuring the size of silicon grains:
[0132] Acquire XRD patterns. Following the equipment and methods outlined in BTRTC / ZY / 02-008 "X-ray Diffractometer Test Operation Manual," test the XRD patterns of the material. Equipment test parameters: divergence slit 1.0°, anti-scattering slit 2.0°, receiving slit 9.6°, voltage range 40KV, current 40mA, scanning range 10-90°, scan step 0.01313, continuous scanning mode, scan time per step 10.2s. Calculate the wavelength. Calculate the silicon grain size. Use Xpert High Score software to fit and analyze the Si peaks in the XRD, and read the full width at half maximum (FWHM) and peak position of the Si characteristic peak at approximately 28°. Substitute these data into the Scherrer formula to calculate the average silicon grain size.
[0133] (12) Capacity retention test after high-temperature storage:
[0134] The negative electrode material prepared in this application was mixed with graphite material (BTR X4-2, a product of BTR Corporation) to form an active material with a specific capacity of 450 mAh / g. A negative electrode sheet was prepared according to a formulation of active material: binder: conductive agent = 95.1:3.4:1.5. The positive electrode was prepared using high-nickel NMC product M2-C2 (produced by BTR Corporation), with a formulation of M2-C2: binder: conductive agent = 96.6:1.4:2.0. The positive and negative electrode sheets were then wound to form 18650 cylindrical cells. After aging, electrolyte injection, formation, and capacity testing, the cells formed a cylindrical battery. The battery design parameters were: positive electrode compaction density 3.4 g / cm³. 3 The negative electrode compaction density is 1.65 g / cm³. 3 Negative electrode surface density 200g / m³ 2 The capacity ratio (N / P ratio) of the negative electrode to the positive electrode is designed to be 8.2%.
[0135] The prepared battery was charged to 4.2V at a current density of 0.5C, then discharged to 2.7V at 0.5C, and the discharge capacity was recorded as C0. It was then charged to 4.2V again at a current density of 0.5C and stored in a 60℃ constant temperature chamber for 15 days. The battery was then removed and discharged to 2.7V at 0.5C, and the discharge capacity was recorded as C1. Therefore, the capacity retention rate after 15 days of high-temperature storage is C1 / C0.
[0136] Specific capacity and first-efficiency test:
[0137] A negative electrode slurry was prepared using a planetary disperser from Thinking (Japan) with a mass ratio of 70:15:15 for the negative electrode material, conductive carbon black, and polyphthalamide (PPA). The prepared slurry was coated onto a 12μm copper foil and dried to form the negative electrode sheet. A lithium metal sheet was used as the counter electrode, and coin cells (model 2016) were assembled in an Ar-filled glove box. Charge-discharge tests were conducted on the coin cells at a current density of 0.1C within a charge-discharge range of 0.01-1.5V to obtain the initial reversible specific capacity and initial coulombic efficiency. Four parallel samples were prepared for each material during the charge-discharge test, and the median value of the four samples was taken as the coin cell result for that negative electrode material.
[0138] The embodiments of the present invention will be further described below with reference to several examples. However, the embodiments of the present invention are not limited to the specific embodiments described below. Appropriate modifications can be made within the scope of the original claims.
[0139] Example 1
[0140] (1) Add metallic silicon powder and silicon dioxide to a vacuum reactor at a molar ratio of 1.1:1. After evacuating to 30 Pa, heat the vacuum reactor to 1300 °C at a heating rate of 8 °C / min and react for 50 min. Then, introduce ZnS gas at a rate of 5 L / min and a carrier gas introduction rate of 50 L / min and continue the doping reaction for 30 min. Finally, cool the mixture to room temperature at a cooling rate of 100 °C / min to obtain the bulk material.
[0141] (2) The bulk material was crushed and pulverized to obtain particles with D50 = 5 μm. 1 kg of particles were placed in a fluidized bed apparatus, the carrier gas was turned on and the flow rate was set to 10 L / min. After heating to 800 °C, magnesium vapor was introduced at a rate of 4 L / min. After the secondary doping reaction for 6 h, the gas was switched to a mixture of acetylene and ammonia. Acetylene was introduced into the reaction chamber at a rate of 3 L / min, and the volume ratio of ammonia to acetylene was 0.8. After gas phase carbon coating treatment for 8 h, the mixture was naturally cooled to room temperature. Then, after dispersing, demagnetizing, and sieving, the negative electrode material was obtained.
[0142] The negative electrode material obtained in this application includes a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material. The silicon-based active material includes silicon oxide and magnesium silicate, and the negative electrode material contains Zn.
[0143] Example 2
[0144] Unlike Example 1:
[0145] In step (1), the bulk material is obtained by cooling it to room temperature at a cooling rate of 50℃ / min, while the other steps remain unchanged.
[0146] Example 3
[0147] Unlike Example 1:
[0148] In step (1), the bulk material is obtained by cooling it to room temperature at a cooling rate of 120℃ / min, while the other steps remain unchanged.
[0149] Example 4
[0150] Unlike Example 1:
[0151] In step (1), the dopant source is introduced at a rate of 10 L / min, while the other steps remain unchanged.
[0152] Example 5
[0153] The difference from Example 4 is:
[0154] In step (1), the bulk material is obtained by cooling it to room temperature at a cooling rate of 120℃ / min, while the other steps remain unchanged.
[0155] Example 6
[0156] Unlike Example 1:
[0157] In step (1), AsN gas is introduced at a rate of 5 L / min, and the carrier gas is introduced at a rate of 50 L / min. The reaction continues for 30 min, and other steps remain unchanged.
[0158] Example 7
[0159] Unlike Example 1:
[0160] In step (1), GaAs gas is introduced at a rate of 5 L / min, and the carrier gas is introduced at a rate of 50 L / min. The reaction continues for 30 min, and the other steps remain unchanged.
[0161] Example 8
[0162] Unlike Example 1:
[0163] In step (1), Sb gas is introduced at a rate of 5 L / min, and the carrier gas is introduced at a rate of 50 L / min. The reaction continues for 30 min, and other steps remain unchanged.
[0164] Example 9
[0165] Unlike Example 1:
[0166] In step (1), SnS gas is introduced at a rate of 5 L / min, and the carrier gas is introduced at a rate of 50 L / min. The reaction continues for 30 min, and other steps remain unchanged.
[0167] Example 10
[0168] Unlike Example 1:
[0169] In step (1), Ag3N gas is introduced at a rate of 5 L / min, and the carrier gas introduction rate is 50 L / min. The reaction continues for 30 min, and other steps remain unchanged.
[0170] Example 11
[0171] The difference from Example 2 is:
[0172] In step (2), the reaction time for introducing acetylene is adjusted to 5 hours, and the reaction temperature for acetylene is adjusted to 600°C. Other steps remain unchanged.
[0173] Example 12
[0174] Unlike Example 1:
[0175] In step (2), the reaction time for introducing acetylene is adjusted to 10 hours, and the reaction temperature of acetylene is adjusted to 1000°C. Other steps remain unchanged.
[0176] Example 13
[0177] The difference from Example 1 is that the doping source introduction rate was adjusted to 10 L / min, and the doping reaction time was adjusted to 80 min. All other steps remained the same.
[0178] In step (1),
[0179] Example 14
[0180] The difference from Example 1 is that the doping source introduction rate was adjusted to 10 L / min. All other steps remained the same.
[0181] Example 15
[0182] The difference from Example 13 is that in step (2), the reaction temperature for introducing acetylene is adjusted to 1000°C. The other steps remain unchanged.
[0183] Example 16
[0184] The difference from Example 14 is that in step (2), the reaction time for introducing acetylene is adjusted to 3 hours. The other steps remain unchanged.
[0185] Comparative Example 1
[0186] (1) Add metallic silicon powder and silicon dioxide into a vacuum reactor at a molar ratio of 1.1:1. After evacuating to 30 Pa, heat the vacuum reactor to 1300 °C at a heating rate of 8 °C / min and react for 50 min. Then cool to room temperature at a cooling rate of 100 °C / min to obtain bulk material.
[0187] (2) The bulk material was crushed and pulverized to obtain particles with D50 = 5 μm. 1 kg of particles were placed in a fluidized bed apparatus, the carrier gas was turned on and the flow rate was set to 10 L / min. After heating to 800 °C, magnesium vapor was introduced at a rate of 4 L / min. After reacting for 6 h, the gas introduced was switched to a mixture of acetylene and ammonia. Acetylene was introduced into the reaction chamber at a rate of 3 L / min, and the volume ratio of ammonia to acetylene was 0.8. After continuing the reaction for 8 h, the mixture was naturally cooled to room temperature to obtain the composite silicon-oxygen material.
[0188] (3) The composite silicon-oxygen material is broken down, demagnetized, and sieved to obtain the negative electrode material.
[0189] Comparative Example 2
[0190] (1) Add metallic silicon powder and silicon dioxide into a vacuum reactor at a molar ratio of 1.1:1. After evacuating to 30 Pa, heat the vacuum reactor to 1300 °C at a heating rate of 8 °C / min and react for 50 min. Then, allow it to cool naturally to room temperature to obtain bulk material.
[0191] (2) The bulk material was crushed and pulverized to obtain particles with D50 = 5 μm. 1 kg of particles were placed in a fluidized bed apparatus, the carrier gas was turned on and the flow rate was set to 10 L / min. After heating to 800 °C, magnesium vapor was introduced at a rate of 4 L / min. After reacting for 6 h, the gas introduced was switched to a mixture of acetylene and ammonia. Acetylene was introduced into the reaction chamber at a rate of 3 L / min, and the volume ratio of ammonia to acetylene was 0.8. After continuing the reaction for 8 h, the mixture was naturally cooled to room temperature to obtain the composite silicon-oxygen material.
[0192] (3) The composite silicon-oxygen material is broken down, demagnetized, and sieved to obtain the negative electrode material.
[0193] Comparative Example 3
[0194] Unlike Example 1, in step (2), no nitrogen source gas is added to the carbon source, while the other steps remain unchanged.
[0195] The test results are detailed in Tables 1 and 2.
[0196] Table 1. Test results of negative electrode material performance
[0197]
[0198]
[0199] Table 2 Performance test results of negative electrode materials and batteries
[0200]
[0201] According to the test data from Examples 1 to 16 (abbreviated as S1 to S16), the surface flexibility of the negative electrode material is within the range of 0.08 to 0.5, which can ensure sufficient lithium intercalation of the silicon-based active material and withstand the volume expansion and contraction of the silicon-based active material, reducing the generation of surface cracks in the negative electrode material. The negative electrode material possesses excellent initial coulombic efficiency and specific capacity, while also improving storage capacity retention. When the surface flexibility R is within a suitable range, the capacity retention of the battery made from the negative electrode material is above 95%. When the surface flexibility R exceeds the specified range, the storage performance of the battery decreases significantly.
[0202] According to the test data from Examples 11-12 (abbreviated as S11-S12), the area ratio A of the first characteristic peak to the second characteristic peak of the anode material has a significant impact on the initial coulombic efficiency of the anode material. The larger the value of A, the lower the initial efficiency of the anode material; this indicates that there are too many defects in the carbon material on the surface of the silicon-based active material, which is not conducive to the coulombic efficiency of the anode material.
[0203] According to the test data of Examples 13-14 (abbreviated as S13-S14), the average mechanical strength Fa of the negative electrode material is related to the storage capacity retention rate. In Example 13, the increased Fa value indicates higher surface strength of the negative electrode material. However, this also leads to decreased surface stability when facing the expansion stress of the core silicon-based active material, resulting in more SEI repair during storage and a lower storage capacity retention rate.
[0204] According to the test data from Examples 15-16 (abbreviated as S15-S16), the coefficient of change of thermal conductivity α of the negative electrode material is related to the storage performance of the negative electrode material. The smaller the coefficient of change of thermal conductivity α of the negative electrode material, the weaker the heat dissipation capacity inside the negative electrode material, and the easier it is for heat accumulation to occur inside the negative electrode material. Uneven heat distribution inside leads to large differences in lithium-ion diffusion rates, resulting in faster capacity loss.
[0205] Compared to the test data of Example 1, Comparative Example 1 (abbreviated as D1) did not dope the silicon-based active material with metal element T. The surface flexibility R of the negative electrode material was too low, and the carbon material layer on the surface of the negative electrode material was more brittle. It was more likely to crack and break when faced with greater external force. Similarly, the SEI film would be repeatedly generated, the irreversible consumption of active lithium ions would increase, and the capacity decay would be accelerated during storage.
[0206] Compared to the test data of Example 1, Comparative Example 2 (D2) showed that the surface flexibility R of the negative electrode material in Comparative Example 1 was too low, which also led to accelerated capacity decay during storage. This is because Comparative Example 2 did not control the cooling rate during the preparation process, resulting in a reduction in the average mechanical strength Fa and a decrease in battery storage performance.
[0207] Compared with the test data of Example 1, the negative electrode material of Comparative Example 3 (abbreviated as D3) did not have nitrogen source gas added to the carbon source during the preparation process. The carbon layer on the surface of the silicon-based active material had fewer defects. Although the mechanical strength of the negative electrode material was improved, its brittleness increased. The surface flexibility of the negative electrode material was poor. The capacity retention rate of the battery prepared by the negative electrode material decreased significantly after 15 days of storage.
[0208] Although this application discloses preferred embodiments as described above, it is not intended to limit the claims. Any person skilled in the art can make several possible changes and modifications without departing from the concept of this application. Therefore, the scope of protection of this application should be determined by the scope defined in the claims of this application.
Claims
1. A negative electrode material, characterized in that, The negative electrode material includes a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material. The silicon-based active material includes silicon and oxygen elements. The negative electrode material also contains a metal element T, which is selected from at least one of Zn, Ga, As, Sb, Sn, and Ag. The mechanical strength of the negative electrode material was tested using atomic force microscopy, and the average mechanical strength of the negative electrode material was Fa GPa. The negative electrode material was tested using Raman spectroscopy, and the negative electrode material was measured at 1345 cm⁻¹. -1 ~1365cm -1 The first characteristic peak exists within the wavelength range, at 1570 cm⁻¹. -1 ~1610cm -1 A second characteristic peak exists within the wavelength range, and the average value of the peak area ratio between the first characteristic peak and the second characteristic peak is A; The surface flexibility of the negative electrode material is R = A / Fa, where 0.08 ≤ R ≤ 0.
5.
2. The negative electrode material according to claim 1, characterized in that, 3≤Fa≤15; and / or, 1.2≤A≤2.
5.
3. The negative electrode material according to claim 1, characterized in that, The thermal conductivity of the negative electrode material is g1 W / (m·K) at 100℃ and g2 W / (m·K) at 600℃. The coefficient of change of thermal conductivity of the negative electrode material is σ=(g2-g1) / 500, and 0.03%<σ<0.5%.
4. The negative electrode material according to claim 3, characterized in that, 0.18≤g1≤0.34; and / or, 0.5≤g2≤2.
5.
5. The negative electrode material according to any one of claims 1 to 3, characterized in that, The hybridization degree ε of the negative electrode material is ε = K2 / K1, where K2 is the position of the highest peak intensity of the silicon characteristic peak measured by Raman spectroscopy, and K1 is the crystal orientation. <111> The position of the highest peak intensity of silicon characteristic peaks measured by Raman spectroscopy on a single-crystal silicon wafer, 0.8≤ε<1.
6. The negative electrode material according to claim 5, characterized in that, The mass content of the metallic element T in the negative electrode material is ≤300ppm.
7. The negative electrode material according to claim 1, characterized in that, The negative electrode material also includes other non-metallic elements; it satisfies at least one of the following characteristics: (1) The other non-metallic elements include at least one of hydrogen and nitrogen, and the ratio of the number of carbon atoms to the total number of hydrogen and nitrogen atoms in the negative electrode material is (3-10):1; (2) The other non-metallic elements include sulfur, and the ratio of the number of carbon atoms to the number of sulfur atoms in the negative electrode material is (2500-6500):1; (3) The carbon material includes at least one of amorphous carbon and graphitized carbon; (4) The carbon material forms a carbon layer on at least part of the surface of the silicon-based active material, and the thickness of the carbon layer is <500nm.
8. The negative electrode material according to claim 1, characterized in that, It satisfies at least one of the following characteristics: (1) The silicon-based active material includes at least one of elemental silicon, silicon oxide and silicate; (2) The silicon-based active material includes silicon oxide, and the general chemical formula of the silicon oxide is SiO₂. x , 0 < x ≤ 2; (3) The silicon-based active material also includes at least one of silicates of element M and oxides of element M, wherein element M is selected from at least one of Mg, Al and Li; (4) The average particle size of silicon grains in the negative electrode material is <20nm.
9. The negative electrode material according to any one of claims 1 to 8, characterized in that, The negative electrode material satisfies at least one of the following characteristics: (1) The water content in the negative electrode material is <0.5% by mass; (2) The tap density of the negative electrode material is > 0.5 g / cm³. 3 ; (3) The powder conductivity of the negative electrode material under 20kN pressure is >0.5S / cm.
10. A battery, characterized in that, Includes the negative electrode material as described in any one of claims 1 to 9.
